In Vitro Efficacy of Tulsi (Ocimum sanctum) based Extract against Soil Borne Fungi - Kaur, Parneet; Sharma, Indu; Kumar, Rahul; Sharma, Sonika; Shiwani, Kumari; Sharma, Aditi; Sharma, Ashutosh (International Journal of Economic Plants, 2024)
In the present study, antifungal effect of different concentrations of aqueous Tulsi (Ocimum sanctum) extract and Tulsi-AgNO3 mix was tested in vitro against Alternaria, Fusarium and Rhizoctonia. The study was conducted from February to November in the year 2020. Overall results suggested that Tulsi extract significantly inhibited (above 70%) the mycelial growth of soil borne fungi. Highest concentration of Tulsi extract resulted in 77.43% growth inhibition against Alternaria solani and 76.75% inhibition of Rhizoctonia solani. Tulsi-AgNO3 showed less inhibition of pathogenic fungi compared to the treatments where only Tulsi extract was used. Results show a dose-dependent inhibition of radial growth across all fungi, with Alternaria spp. displaying the highest sensitivity, achieving over 58% inhibition at 1000 ppm. In contrast, Rhizoctonia solani exhibited the lowest sensitivity, with inhibition percentages peaking at 29.64% at 1000 ppm. These findings suggest that the Tulsi extract is a promising antifungal agent, although its efficacy varies by fungal species, indicating the potential need for targeted or combination treatments for effective pathogen control.